The Relation Between Disease Activity, Patient‐Reported Outcomes, and Grip Force Over Time in Early Rheumatoid Arthritis. Issue 8 (19th August 2019) - Rydholm, Maria; Wikström, Ingegerd; Hagel, Sofia; Jacobsson, Lennart T. H.; Turesson, Carl
Abstract : Objective: The objective of this study is to identify early predictors of future reduced grip force in patients with rheumatoid arthritis (RA) and to identify early predictors of grip force over time. Methods: In a structured follow‐up of an inception cohort of patients with early RA, average grip force values of the dominant hand were evaluated and compared with the expected based on age‐ and sex‐specific reference values. Potential predictors of reduced grip force (less than 50% of expected) at 5 years were examined using logistic regression. Differences in percentage of expected grip force values over the study period and differences in change over time, by baseline disease parameters, were estimated using mixed linear‐effects models. Results: Among 200 patients with early RA, 44% had reduced grip force 5 years after diagnosis. Baseline characteristics that predicted reduced grip force at 5 years included high scores for the Health Assessment Questionnaire Disability Index (odds ratio 1.54 per SD; 95% confidence interval 1.13‐2.11), high scores for pain and patient global assessment, and low grip force. C‐reactive protein levels, the erythrocyte sedimentation rate, the 28‐joint Disease Activity Score (DAS28), rheumatoid factor, anti–cyclic citrullinated peptide antibodies, joint counts, and synovitis of individual joints in the dominant upper extremity did not predict reduced grip force. Patients with baseline synovitis of the wrist or metacarpophalangeal joints or patients with a high DAS28 had lower estimated grip force at inclusion but also greater improvement of grip force over time. Conclusion: Patient‐reported outcomes predicted reduced grip strength 5 years after diagnosis. This underlines the prognostic importance of disability in early RA. Joint counts and synovitis in individual joints may change rapidly in early RA and appear to be less predictive of long‐term hand function.